The Application of Dynamic Compaction on Marjan Island - Hamidi, Babak; Nikraz, Hamid; Varaksin, Serge (The Australian Geomechanical Society and New Zealand Geotechnical Society, 2012)
Marjan Island is 2.7 million m2 of development located 27 km southwest of Ras Al Khaimah in the United Arab Emirates. This project has been reclaimed from the Persian Gulf by tipping sand into the sea. Geotechnical investigations indicated that the upper 7 m of ground was composed of very loose to medium dense silty sand interbedded with layers of boulders at different depths. SPT blow counts were recorded to be as low as 4 and Menard Pressuremeter Test (PMT) limit pressure was as low as 70 kPa. Fines content was from 13 to 30%. Preliminary calculations suggested that the in-situ ground conditions could not satisfy the island’s main road’s settlement criteria and that ground improvement was required. Thus, 198,000 m2 of the reclamation was treatment by Dynamic Compaction. Pounders weighing up to 20 tons were dropped from 20 m to compact the loose soil. 32 PMT were carried out after ground improvement to verify the achievements. These tests were able to demonstrate that acceptance criteria was readily achieved and that on average the soil’s modulus of deformation increased by more than 400%.